Penguatan Media Digital dan Pengembangan Strategi Intelektual Melalui Kegiatan Interaktif Bernuansa Budaya Lokal Di Yayasan Amara Bhawana Sastra - I Nyoman Bagus Pramartha; Komang Hari Santhi Dewi; Wayan Andrika Putera; I Kadek Sandy Dwiartha Putra; Mario Antonius Seda Mbei; I Gede Angga Bagus Aditya; Ni Made Tara Dwitya Putri; Ni Putu Anggi Amelia Ardan (Universitas Mataram, 2026)
This community service program aims to strengthen digital media integration and enhance pedagogical competencies among teachers at the Amara Bhawana Sastra Foundation in Bangli, Bali. The program was initiated to address two critical gaps identified through preliminary observations: the absence of a professional institutional website for donor outreach and limited teacher proficiency in utilizing culture-based instructional media. The intervention involved a dual-faceted approach: the development of an official website and intensive training on the